Facile Preparation and Photoinduced Superhydrophilicity of Highly Ordered Sodium-Free Titanate Nanotube Films by Electrophoretic Deposition - Minghua Zhou; Huogen Yu (International Journal of Photoenergy)
Highly ordered sodium-free titanate nanotube films were one-step prepared on F-doped SnO2-coated (FTO) glass via an electrophoretic deposition method by using sodium titanate nanotubes as the precursor. It was found that the self-assembled formation of highly ordered sodium titanate nanotube films was accompanied with the effective removal of sodium ions in the nanotubes during the electrophoretic deposition process, resulting in the final formation of protonated titanate nanotube film. With increasing calcination temperature, the amorphous TiO2 phase is formed by a dehydration process of the protonated titanate nanotubes at 300°C and further transforms into anatase TiO2 when the calcination temperature is higher than 400°C. Compared with the as-prepared titanate nanotube film, the calcined titanate nanotube film (300–600°C) exhibits attractive photoinduced superhydrophilicity under UV-light irradiation. In particular, 500°C-calcined films show the best photoinduced superhydrophilicity, probably due to synergetic effects of enhanced crystallization, surface roughness, and ordered structures of the films.